A functional profile of Left Dislocation in Biblical Hebrew - Westbury, Josh (Stellenbosch Papers in Linguistics Plus, 2016)
The primary aim of this paper is to provide a functional profile of verbal Left Dislocation (=LD) constructions in the Torah and Former Prophets (Genesis–2Kings). As a precursor, however, an abbreviated syntactico-semantic description of LD constructions within the aforementioned corpus is provided. This description consists of seven overlapping constructional schemas (i.e. construction types) that form a radial network around a typologically prototypical schema. Accordingly, each schematic type is more or less prototypical depending on its family resemblance (i.e. shared attributes) to the prototype. In light of this formal profile, and of the fact that grammatical constructions are equal parts form and function, the remainder and central focus of the paper will entail a detailed functional explanation of LD. This functional profile will consist of two complementary parts: 1) the central factors motivating the use of LD, and 2) the prototypical and non-prototypical discourse-pragmatic functions achieved by the construction in discourse. Together with the formal description, this functional explanation reveals a textured profile of the LD category, one that consists of a unified radial network of overlapping constructional types.